Increased urine IgM excretion predicts cardiovascular events in patients with type 1 diabetes nephropathy - Torffvit Ole (BMC Medicine, 2009)
Abstract Background Diabetic nephropathy, a major complication of diabetes, is characterized by progressive renal injury and increased cardiovascular mortality. An increased urinary albumin excretion due dysfunction of the glomerular barrier is an early sign of diabetic nephropathy. An increased urinary excretion of higher molecular weight proteins such as IgM appears with progression of glomerular injury. We aim here to study the prognostic significance of urine IgM excretion in patients with type 1 diabetes mellitus (type 1 diabetic nephropathy). Methods This is an observational study of 139 patients with type1 diabetes mellitus (79 males and 60 females) under routine care at the diabetic outpatient clinic at the Lund University Hospital. The median follow-up time was 18 years (1 to 22) years. Urine albumin and urine IgM concentration were measured at time of recruitment. Results Overall 32 (14 male and 18 female) patients died in a cardiovascular event and 20 (11 male and 9 female) patients reached end-stage renal disease. Univariate analysis indicated that patient survival and renal survival were inversely associated with urine albumin excretion (RR = 2.9 and 5.8, respectively) and urine IgM excretion (RR = 4.6 and 5.7, respectively). Stratified analysis demonstrated that in patients with different degrees of albuminuria, the cardiovascular mortality rate and the incidence of end-stage renal disease was approximately three times higher in patients with increased urine IgM excretion. Conclusion An increase in urinary IgM excretion in patients with type 1 diabetes is associated with an increased risk for cardiovascular mortality and renal failure, regardless of the degree of albuminuria.